Moral Conflict in the Novel Der Vorleser by Bernhard Schlink: a Study of John Stuart Mill’s Utilitarianism - Beni Hadi Ramadhan; Isti Haryati (Universitas Negeri Malang, 2025)
This research aims to identify and explain the forms of moral conflict in the novel Der Vorleser by Bernhard Schlink using John Stuart Mill’s theory of utilitarianism. The research employs a qualitative method with a philosophical approach. Data were collected through close reading and note-taking techniques from the novel, and analyzed using semantic validity as well as intrarater and interrater reliability. The findings reveal four main types of moral conflict experienced by the main character: (1) the conflict between individual obligations and public interests, where Michael is faced with a dilemma between keeping personal secrets and fighting for justice, (2) the conflict between short-term and long-term values, which is seen in Michael's decision to remain silent in Hanna's trial and the long-term consequences that accompany it, (3) The conflict between higher and lower happiness, which reflects the dilemma between emotional satisfaction and the moral responsibility that Michael must take. (3) The conflict between intentions and consequences of actions, where the actions taken by the characters often lead to undesirable results despite having good intentions